Psychosocial Correlates of Mental Health and Well-Being During the COVID-19: The Spanish Case - Esteban-Gonzalo, Sara; González-Pascual, Juan Luis; Caballero-Galilea, María; Esteban-Gonzalo, Laura (Frontiers in Psychology, 2020)
Background. The COVID-19 pandemic has hit almost all countries around the globe, seriously affecting the welfare of populations. Spain is especially hard-hit. In this context, the purpose of the present study is to analyze social, demographic and economic correlates of mental health during the COVID-19 pandemic in the population residing in Spain. Method. The sample of this cross-sectional study was comprised of 801 participants aged 18 or older and residing in Spain. Data collection was carried out during March and April 2020. Data of mental health (GHQ12) and wellbeing (Positive and Negative Affect Schedule) indicators, as well as of a wide number of social, demographic and economic variables were recorded. Linear regression models were built to value associations between mental health and social, demographic and economic indicators. Results. Mental health morbidity was higher in women, younger people, individuals with medium studies, people with fewer children, singles, students and unemployed individuals. Positive affect was higher among women, people with a high level of studies, those not co-living with dependent seniors, the self-employed, the employed and those working outside home. Negative affect was negatively associated to age and number of children, and was higher among women, people with basic studies, singles, individuals co-living with dependent seniors, homemakers and students. Conclusions. The most vulnerable populations were found to be women, younger people, people with basic or medium studies, students and individuals with no remunerated activities, single populations and those co-living with dependent seniors as well as those with a reduced number of children.